2021
DOI: 10.1001/jama.2021.11945
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mortality From COVID-19 and Other Leading Causes of Death Among Latino vs White Individuals in Los Angeles County, 2011-2020

Abstract: This study compares age-adjusted mortality rates before and during the COVID-19 pandemic (2011-2020) among Latino and White individuals living in Los Angeles County.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 4 publications
(4 reference statements)
5
33
0
Order By: Relevance
“…The Hispanic Covid-19 death rate in 2020 was around 1.1 times higher than the Black death rate and 2.3 times higher than the White death rate. These findings are consistent with other evidence that has emerged surrounding the particularly adverse impact of the pandemic on Hispanic mortality ( Riley et al, 2021 ; Rodriguez-Diaz et al, 2020 ; Simon et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Hispanic Covid-19 death rate in 2020 was around 1.1 times higher than the Black death rate and 2.3 times higher than the White death rate. These findings are consistent with other evidence that has emerged surrounding the particularly adverse impact of the pandemic on Hispanic mortality ( Riley et al, 2021 ; Rodriguez-Diaz et al, 2020 ; Simon et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…A large body of research has shown how structural and systemic racism during the pandemic has routinely disadvantaged communities of color by placing these communities at heightened risk of Covid-19 incidence ( Bailey et al, 2021 ; Garcia et al, 2021 ; McClure et al, 2020 ). Hispanic individuals are disproportionately represented in essential occupations with high-exposure to Covid-19 and limited workplace protections ( Rodriguez-Diaz et al, 2020 ; Simon et al, 2021 ). Additionally, Hispanic populations are more likely to live in denser, multigenerational households, magnifying the effect of occupational exposure ( Macias Gil et al, 2020 ; Riley et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hispanic communities had the highest Covid-19 death rate in 2020, around 1.1 times higher than their Black peers and 2.3 times higher than their White peers, driving a nearly 40% increase in all-cause mortality in the Hispanic populations, relative to around 27% and 13% for Black and White populations, respectively (Table 2). These findings are consistent with other emerging evidence of the particularly adverse impact of the pandemic on Hispanic mortality (Riley et al, 2021;Rodriguez-Diaz et al, 2020;Simon et al, 2021). This pattern undermines established understandings of the "Hispanic Mortality Paradox," or the historical tendency for Hispanic individuals to have better mortality outcomes than their non-Hispanic White counterparts despite their lower socioeconomic position (Ruiz et al, 2013).…”
Section: High Covid-19 Mortality Among Hispanic Communitiessupporting
confidence: 82%
“…Hispanic communities have the lowest rate of health insurance coverage of any racial/ethnic group in the United States, with nearly 20% uninsured, compared to just 5% of the White population (Macias Gil et al, 2020). Additionally, language barriers, distrust and fear of healthcare institutions driven by broader anti-immigrant rhetoric and policy, and underlying financial hardship faced by Hispanic individuals, particularly those in the immigrant community, have all been linked to worse healthcare access and quality, potentially amplifying the impact of Covid incidence on mortality outcomes (Macias Gil et al, 2020;Riley et al, 2021;Rodriguez-Diaz et al, 2020;Simon et al, 2021). These health care barriers, coupled with a higher prevalence of comorbid conditions, such as diabetes and heart disease, likely worsen Covid-19 outcomes in the Hispanic community once infected (Kim & Hales, 2021;Simon et al, 2021) High Mortality from Non-Covid-19 Causes of Death Among Black Individuals Despite having levels of Covid incidence and mortality below those of Hispanic individuals, Black individuals saw the largest absolute increase in all-cause mortality, a pattern that emerged in another large national study (Miller et al, 2021).…”
Section: High Covid-19 Mortality Among Hispanic Communitiesmentioning
confidence: 99%
“…Prior to the pandemic, the city of Los Angeles reported lower rates of mortality among Latin American individuals compared to other ethnic groups; this situation reversed in 2020, with the rate of death among the Latin American population increasing to 714 per 100,000, while the death rate of non-Latin American people was only 699 per 100,000. COVID-19 was identified as the leading cause of death among Latin Americans [ 17 ]. Conversely, in other cohort studies, Ogedegbe et al [ 14 ], Kabarriti et al [ 15 ], and Rodriguez et al [ 16 ] reported that the rates of adverse outcomes of COVID-19 did not differ by race/origin after adjustment for sociodemographic and clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%